Comparison of Shifts in Skeletal Muscle Plasticity Parameters in Horses in Three Different Muscles, in Answer to 8 Weeks of Harness Training - de Meeûs d'Argenteuil, Constance; Boshuizen, Berit; Vidal Moreno de Vega, Carmen; Leybaert, Luc; de Maré, Lorie; Goethals, Klara; De Spiegelaere, Ward; Oosterlinck, Maarten; Delesalle, Cathérine (Frontiers in Veterinary Science, 2021)
Training-induced follow-up of multiple muscle plasticity parameters in postural stability versus locomotion muscles provides an integrative physiological view on shifts in the muscular metabolic machinery. It can be expected that not all muscle plasticity parameters show the same expression time profile across muscles. This knowledge is important to underpin results of metabolomic studies. Twelve non-competing Standardbred mares were subjected to standardized harness training. Muscle biopsies were taken on a non-training day before and after 8 weeks. Shifts in muscle fiber type composition and muscle fiber cross-sectional area (CSA) were compared in the m. pectoralis, m. vastus lateralis and m. semitendinosus. In the m. vastus lateralis which showed most pronounced training-induced plasticity, two additional muscle plasticity parameters (capillarization and mitochondrial density) were assessed. In the m. semitendinosus additionally the mean minimum Feret’s diameter was assessed. There was a significant difference in baseline profiles. The m. semitendinosus contained less type I and more type IIX fibers compatible with the most pronounced anaerobic profile. Though no baseline fiber type specific and overall mean CSA differences could be detected, there was a clear post-training decrease in fiber type specific CSA, most pronounced for the m. vastus lateralis and this was accompanied by a clear increase in capillary supply. No shifts in mitochondrial density were detected. The m. semitendinosus showed a decrease in fiber type specific CSA of type IIAX fibers and a decrease of type I fiber Feret’s diameter as well as mean minimum Feret’s diameter. The training-induced increased capillary supply in conjunction with a significant decrease in muscle fiber CSA suggest that the muscular machinery models itself towards an optimal smaller individual muscle fiber structure to receive and process fuels that can be swiftly delivered by the circulatory system. These results are interesting in view of recently identified important fuel candidates such as branched-chain amino acids, aromatic amino acids and gut microbiome-related xenobiotics, which need a rapid gut-muscle gateway to reach these fibers and are less challenging for the mitochondrial system. More research is needed with that respect. Results also show important differences between muscle groups with respect to baseline and training-specific modulation.